ANALISIS PENGGUNAAN MOTOR INDUKSI PADA SISTEM KONVEYOR INDUSTRI - Ranses Wahyudi Sijabat; Zuraidah Tharo; Haris Gunawan (Jurnal Nasional Teknologi Komputer, 2025)
In the modern industrial world, conveyor systems are important components that support the efficiency and sustainability of the production process. The use of induction motors as conveyor drives has become the main choice because of its durability, energy efficiency, and relatively low operational costs. This study aims to analyze the performance of induction motors, especially three-phase induction motors, in belt conveyor systems in industrial environments. The method used is a quantitative descriptive approach by analyzing technical parameters such as motor power, efficiency, power factor, torque, and operational and maintenance data. The results of the study show that a three-phase induction motor with a power of 1.5 kW provides more stable and efficient performance than a single-phase motor of 0.75 kW, both in terms of energy consumption, torque efficiency, and operational efficiency. The efficiency of the three-phase motor is recorded at 88% with energy consumption of ±85 kWh per month in a work cycle of ±200 hours. With a maximum torque of 6.0 Nm, the motor is able to overcome inertia loads optimally. It is concluded that the selection of three-phase induction motors that are in accordance with the needs of the conveyor system can improve energy efficiency and extend the operational life of industrial equipment.